Dynamic programmable surface and preparation method thereof
The preparation of liquid crystal elastomer fibers through wet spinning technology and combined with electrospinning technology and liquid metal arrays has solved the shortcomings of deformable surfaces in the prior art in fine structure control and low voltage regulation, and achieved efficient and sensitive capabilities Deformed surfaces have wide application potential.
Patent Information
- Application Number
- CN202411565740.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The existing deformable surfaces have shortcomings in fine structural control, making it difficult to achieve independent regulation at low voltages, and the existing regulation methods mostly rely on large voltages or strong magnetic fields, and cannot achieve independent regulation in multi-modes.
Liquid crystal elastomer fibers are prepared by using wet spinning technology, and nanofiber membranes are prepared using electrospinning technology, combining liquid metal arrays and ultraviolet light cross-linking to achieve a deformable surface driven by voltage and infrared light.
It realizes a deformable surface that actuates rapidly at low voltages, has ultra-sensitive actuation and good deformation capabilities, and can show broad application prospects in soft robots and wearable devices.
Smart Images

Figure CN119408256A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of soft robots and wearable devices, and in particular relates to a dynamic programmable surface and a preparation method thereof. Background Art
[0002] Soft matter that can dynamically reconfigure its shape based on interaction with the environment or perception of information is booming, especially the deformation of thin sheets or two-dimensional (2D) materials into programmable 3D shapes. 2D materials with 3D shapes exist in large quantities in artificial and biological systems and play a variety of functions, such as flowers, leaves, marine invertebrates, etc. Such deformable materials can enable new technologies to be widely used, including soft robots, deployable systems, wearable devices, tissue engineering and biomimetic manufacturing. A variety of materials have been used to prepare deformable surfaces, such as dielectric elastomers and responsive hydrogels, but there is still a lack of rapid control of fine structures. For example, by imitating plant and animal structures through hydrogels, only overall deformation can be achieved, and it is impossible to regulate at a certain point on the surface. Another problem is that existing deformable surfaces often require large regulation voltages or strong magnetic fields. It is still challenging to achieve regulation under low voltages, and independent regulation in multiple modes still needs further exploration. Summary of the invention
[0003] The purpose of the present invention is to provide a dynamic programmable surface and a preparation method thereof in view of the deficiencies in the prior art. The method has a simple process and can be mass-produced. The obtained deformable surface exhibits ultra-sensitive actuation, good deformation ability, and modulatable deformation structure, and shows application potential in soft robots and wearable devices.
[0004] In addition, the method adopted by the present invention is expected to be applied to various types of flexible film materials, such as polyurethane, acrylic polymer, etc.
[0005] The present invention is achieved through the following technical solutions:
[0006] A method for preparing a dynamically programmable surface, the method comprising the following steps:
[0007] (1) adding 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene, 3,6-dioxa-1,8-octanedithiol, pentaerythritol tetrakis-3-mercaptopropionate and benzil dimethyl ether to an organic solvent, stirring evenly, adding di-n-propylamine, sealing, stirring at room temperature, and reacting fully;
[0008] (2) Based on the liquid crystal elastomer precursor solution, the liquid crystal elastomer fibers are prepared by wet spinning technology, and the liquid crystal elastomer fibers are further cross-linked and cured by ultraviolet light;
[0009] (3) Printing a liquid metal array on the surface of the first nanofiber membrane, and then attaching a second nanofiber membrane; collecting the liquid crystal elastomer fibers on the roller, and adhering them to the first nanofiber membrane at the position coated with the liquid metal array, thereby obtaining a voltage-controlled deformable surface.
[0010] Furthermore, it also includes:
[0011] 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene, 3,6-dioxa-1,8-octanedithiol, pentaerythritol tetrakis-3-mercaptopropionate, graphene and benzil dimethyl ether are added to an organic solvent, stirred evenly, and then di-n-propylamine is added, sealed, stirred at room temperature, and fully reacted; step (2) is repeated to obtain liquid crystal elastomer fibers with infrared light responsiveness; and the fibers are arrayed on a first nanofiber film to obtain a deformable surface regulated by infrared light.
[0012] Furthermore, the step (1) is specifically as follows:
[0013] 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene is dissolved in an organic solvent to a final concentration of 0.2-0.25 g / mL, 3,6-dioxa-1,8-octanedithiol and pentaerythritol tetrakis-3-mercaptopropionate are added in a molar ratio of 4.5-5.5:1, and the molar ratio of double bonds to thiol groups is 1.1-1.15:1; benzil dimethyl ether is added to a mass fraction of 1%-2%, and a di-n-propylamine catalyst is added to a volume fraction of 0.3%-0.5%, and the reaction is carried out at room temperature for 24 hours.
[0014] Furthermore, the step (2) is specifically as follows:
[0015] The reaction product in step (1) was poured into a syringe with a needle diameter of 0.9-1.1 mm, and the syringe was placed on a syringe pump, followed by extrusion at a pressure of 0.35 MPa and a speed of 1 mm / min, and collected on a roller with a rotation speed of 5 rpm, and further irradiated with ultraviolet light.
[0016] Furthermore, the first nanofiber membrane and the second nanofiber membrane are both one of polyurethane nanofiber membrane, polylactic acid nanofiber membrane and polymethyl methacrylate nanofiber membrane.
[0017] Furthermore, it also includes an ultraviolet curing device, which is a 365nm curing lamp to achieve the ultraviolet irradiation in step (2).
[0018] Furthermore, the step (3) is specifically as follows:
[0019] A first nanofiber membrane with a thickness of 0.4-0.7 mm is prepared by electrospinning, a liquid metal array is printed on its surface, and a second fiber membrane with a thickness of 0.05-0.15 mm is attached to protect the liquid metal.
[0020] Furthermore, the applied voltage of the voltage-regulated deformable surface is 0.5-1.1V.
[0021] Furthermore, the final concentration of the graphene is 0.4-0.6 mg / mL; the wavelength of the infrared light is 0.76-5 um, and the intensity of the infrared light is 200 mW.
[0022] The dynamically programmable surface prepared according to the above preparation method includes a voltage-controlled deformable surface and an infrared-controlled deformable surface.
[0023] The beneficial effects of the present invention are as follows:
[0024] The present invention uses liquid crystal elastomer as material and uses wet spinning technology to prepare liquid crystal unit oriented elastomer fibers. Earlier reports have prepared liquid crystal elastomer fibers, but they mostly use direct heating methods to drive them, and cannot achieve dual driving modes of voltage and infrared light. We use wet spinning technology to prepare liquid crystal elastomer fibers on a large scale, and simply give them the characteristics of being drivable by low voltage and infrared light.
[0025] The present invention utilizes electrostatic spinning technology to prepare nanofiber membranes and print liquid metal; liquid crystal elastomer fibers can be adhered to the surface of the nanofiber membrane in a variety of array forms to achieve various controllable deformation surfaces.
[0026] The process of the invention is simple and controllable, with a short preparation cycle, safe and pollution-free, and inexpensive. Different three-dimensional deformable surfaces can be flexibly prepared according to actual production requirements, and it has broad application prospects in soft robots and flexible wearable devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative labor.
[0028] Figure 1 This is a schematic diagram of an experimental device for preparing liquid crystal elastomer fibers in step 2 of the present invention;
[0029] Figure 2is a stress-strain curve of the liquid crystal elastomer fiber without further crosslinking obtained by implementing step 2 of Example 5 of the present invention;
[0030] Figure 3 is a schematic diagram of various deformable surfaces provided by an embodiment of the present invention;
[0031] Figure 4 is a schematic diagram of a deformation process of a deformable surface provided by an embodiment of the present invention;
[0032] Figure 5 The height of the protrusions on the deformable surface obtained in Example 9 of the present invention changes with time at a low voltage (1.1 V). DETAILED DESCRIPTION
[0033] The present invention is described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the features of the following embodiments and implementations can be combined with each other.
[0034] The present invention first uses a base-catalyzed thiol-Michael addition reaction to prepare a liquid crystal elastomer precursor solution, then uses a wet spinning technique to prepare liquid crystal elastomer fibers, which are then adhered to a nanofiber membrane prepared by electrospinning to prepare different arrays. By heating the liquid crystal elastomer fibers with liquid metal, rapid actuation at low voltage can be achieved to produce a deformable surface. At the same time, the present invention also provides a method for preparing infrared light-actuated liquid crystal elastomer fibers, and discloses its potential application as an infrared-controlled deformable surface. Compared with traditional additive manufacturing (continuously building 3D structures by depositing materials layer by layer), the method of the present invention can prepare deformable surfaces with different array arrangements on a large scale, has scalability, customizability and deployability, and can open up new strategies for the design and manufacture of shape-deformation engineering systems, including soft robots, deployable systems and bionic devices.
[0035] A method for preparing a dynamically programmable surface of the present invention comprises the following steps:
[0036] (1) adding 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene, 3,6-dioxa-1,8-octanedithiol, pentaerythritol tetrakis-3-mercaptopropionate and benzil dimethyl ether to an organic solvent, stirring evenly, adding di-n-propylamine, sealing, stirring at room temperature, and fully reacting to obtain a liquid crystal elastomer precursor solution;
[0037] (2 as Figure 1 As shown, the reaction product obtained in step (1) is poured into a syringe, and the syringe is fixed on a syringe pump, the syringe is pushed, and the injected liquid crystal elastomer fibers are collected on a drum, and the liquid crystal elastomer fibers are further cross-linked and cured by ultraviolet light to obtain liquid crystal elastomer fibers;
[0038] (3) Printing a liquid metal array on the surface of the first nanofiber membrane, and then attaching a second nanofiber membrane; collecting the liquid crystal elastomer fibers on the roller, and adhering them to the first nanofiber membrane at the position coated with the liquid metal array, thereby obtaining a voltage-controlled deformable surface.
[0039] Preferably, the applied voltage of the voltage-regulated deformable surface is 0.5V.
[0040] Preferably, the organic solvent is tetrahydrofuran solvent THF.
[0041] In some embodiments, step (1) is specifically as follows: dissolving 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene in an organic solvent to a final concentration of 0.2-0.25 g / mL, adding 3,6-dioxa-1,8-octanedithiol and pentaerythritol tetrakis-3-mercaptopropionate in a molar ratio of 4.5-5.5:1, and making the molar ratio of double bonds to thiol groups 1.1-1.15:1; adding benzil dimethyl ether to a mass fraction of 1%-2% and a di-n-propylamine catalyst to a volume fraction of 0.3%-0.5%, and reacting at room temperature for 24 hours.
[0042] In some embodiments, the reaction product in step (1) is poured into a syringe with a needle diameter of 0.9-1.1 mm, the syringe is placed on a syringe pump, and then extruded at a pressure of 0.35 MPa and a speed of 1 mm / min, and collected on a drum with a drum speed of 5 rpm, and further irradiated with ultraviolet light.
[0043] In one embodiment, the ultraviolet light is used to further crosslink and cure the liquid crystal elastomer fibers. Specifically, a 365nm curing lamp is used as an ultraviolet curing device to achieve the ultraviolet light in step (2).
[0044] Preferably, the first nanofiber membrane and the second nanofiber membrane are both one of polyurethane nanofiber membrane, polylactic acid nanofiber membrane and polymethyl methacrylate nanofiber membrane.
[0045] Preferably, the thickness of the first nanofiber membrane is greater than the thickness of the second nanofiber membrane. In some embodiments, the step (3) is specifically as follows: preparing a first nanofiber membrane with a thickness of 0.4-0.7 mm by electrospinning, printing a liquid metal array on its surface, and attaching a second nanofiber membrane with a thickness of 0.05-0.15 mm to protect the liquid metal.
[0046] Another method for preparing a dynamically programmable surface of the present invention comprises:
[0047] 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene, 3,6-dioxa-1,8-octanedithiol, pentaerythritol tetrakis-3-mercaptopropionate, graphene and benzil dimethyl ether are added to an organic solvent, stirred evenly, and then di-n-propylamine is added, sealed, stirred at room temperature, and fully reacted; the above reaction product (i.e., liquid crystal elastomer precursor solution) is poured into a syringe, and the syringe is fixed on a syringe pump, the syringe is pushed, and the injected liquid crystal elastomer fibers are collected on a drum, and the liquid crystal elastomer fibers are further cross-linked and cured by ultraviolet light to obtain cured liquid crystal elastomer fibers with infrared light response performance; the liquid crystal elastomer fibers are arrayed on a first nanofiber membrane to obtain a deformable surface regulated by infrared light.
[0048] Specifically, 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene and graphene are dissolved in an organic solvent to a final concentration of 0.2-0.25 g / mL and 0.4-0.6 mg / mL, respectively, and 3,6-dioxa-1,8-octanedithiol and pentaerythritol tetra-3-mercaptopropionate are added at a molar ratio of 4.5-5.5:1, and the molar ratio of double bonds to thiol groups is 1.1-1.15:1; benzil dimethyl ether is added to a mass fraction of 1%-2%, and a di-n-propylamine catalyst is added to a volume fraction of 0.3%-0.5%, and the reaction is carried out at room temperature for 24 hours. The preparation of the cured liquid crystal elastomer fiber with infrared light responsiveness can refer to the above embodiment, which will not be repeated here.
[0049] In one embodiment, if Figure 3 and Figure 4 As shown, according to the liquid crystal elastomer fibers prepared as described above, by arranging different liquid crystal elastomer fiber arrays, surfaces with different deformation capabilities can be obtained; through a multi-channel controller, digitally controllable reversible three-dimensional deformation of the two-dimensional surface can be achieved.
[0050] Among them, any value in each numerical range in the above embodiments can be selected, and will not be described in detail here.
[0051] Embodiment 1:
[0052] (1) Dissolve the liquid crystal unit RM257 (1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene) in DMF (N,N-dimethylacetamide) to a final concentration of 0.2 g / mL, add 3,6-dioxa-1,8-octanedithiol and pentaerythritol tetra-3-mercaptopropionate in a molar ratio of 5:1, and make the molar ratio of double bonds to mercapto groups 1.1:1. Add 1% by mass of benzil dimethyl ether and 0.4% by volume of di-n-propylamine catalyst, and react at room temperature for 24 hours. Or
[0053] Liquid crystal unit RM257 and graphene were dissolved in DMF to a final concentration of 0.2 g / mL and 0.4 mg / mL, respectively, and 3,6-dioxa-1,8-octanedithiol and pentaerythritol tetra-3-mercaptopropionate were added at a molar ratio of 5:1, and the molar ratio of double bonds to thiol groups was 1.1:1. 1% of benzil dimethyl ether by mass and 0.4% of di-n-propylamine by volume were added as catalysts, and the reaction was carried out at room temperature for 24 hours.
[0054] (2) The reaction product obtained in step (1) is poured into a syringe, and the syringe is fixed on a syringe pump. The syringe is pushed. Since the boiling point of DMF is too high, the solvent cannot evaporate in time and well-formed liquid crystal elastomer fibers cannot be collected.
[0055] Embodiment 2:
[0056] (1) Dissolve the liquid crystal unit RM257 in THF to a final concentration of 0.2 g / mL, add 3,6-dioxa-1,8-octanedithiol and pentaerythritol tetra-3-mercaptopropionate in a molar ratio of 10:1, and make the molar ratio of double bonds to thiol groups 1.1:1. Add 1% by mass of benzil dimethyl ether and 0.4% by volume of di-n-propylamine catalyst, and react at room temperature for 24 hours. Or
[0057] Liquid crystal unit RM257 and graphene were dissolved in DMF to a final concentration of 0.2 g / mL and 0.4 mg / mL, respectively, and 3,6-dioxa-1,8-octanedithiol and pentaerythritol tetra-3-mercaptopropionate were added at a molar ratio of 10:1, and the molar ratio of double bonds to thiol groups was 1.1:1. 1% of benzil dimethyl ether by mass and 0.4% of di-n-propylamine by volume were added as catalysts, and the reaction was carried out at room temperature for 24 hours.
[0058] (2) The reaction product obtained in step (1) is poured into a syringe, fixed on a syringe pump, and the syringe is pushed. Due to insufficient crosslinking agent content, insufficient polymer crosslinking degree, and too low solution viscosity, well-formed liquid crystal elastomer fibers cannot be collected.
[0059] Embodiment 3:
[0060] (1) Dissolve the liquid crystal unit RM257 in THF to a final concentration of 0.2 g / mL, add 3,6-dioxa-1,8-octanedithiol and pentaerythritol tetra-3-mercaptopropionate in a molar ratio of 2:1, and make the molar ratio of double bonds to thiol groups 1.1:1. Add 1% by mass of benzil dimethyl ether and 0.4% by volume of di-n-propylamine catalyst, and react at room temperature for 24 hours. Or
[0061] Liquid crystal unit RM257 and graphene were dissolved in DMF to a final concentration of 0.2 g / mL and 0.4 mg / mL, respectively, and 3,6-dioxa-1,8-octanedithiol and pentaerythritol tetra-3-mercaptopropionate were added in a molar ratio of 2:1, and the molar ratio of double bonds to thiol groups was 1.1:1. 1% of benzil dimethyl ether by mass and 0.4% of di-n-propylamine by volume were added as catalysts, and the reaction was carried out at room temperature for 24 hours.
[0062] (2) The reaction product obtained in step (1) is poured into a syringe and fixed on a syringe pump. The syringe is pushed. However, due to the high content of the crosslinking agent, the degree of polymer crosslinking is too high, and the solution viscosity is too high, the syringe cannot be squeezed out smoothly from the syringe pump.
[0063] Embodiment 4:
[0064] (1) Dissolve the liquid crystal unit RM257 in THF to a final concentration of 0.2 g / mL, add 3,6-dioxa-1,8-octanedithiol and pentaerythritol tetra-3-mercaptopropionate at a molar ratio of 4.5:1, and make the molar ratio of double bonds to thiol groups 1.1:1. Add 1% by mass of benzil dimethyl ether and 0.4% by volume of di-n-propylamine catalyst, and react at room temperature for 24 hours. Or
[0065] Liquid crystal unit RM257 and graphene were dissolved in DMF to a final concentration of 0.2 g / mL and 0.4 mg / mL, respectively, and 3,6-dioxa-1,8-octanedithiol and pentaerythritol tetra-3-mercaptopropionate were added at a molar ratio of 4.5:1, and the molar ratio of double bonds to thiol groups was 1.1:1. 1% of benzil dimethyl ether by mass and 0.4% of di-n-propylamine by volume were added as catalysts, and the reaction was carried out at room temperature for 24 hours.
[0066] (2) Pour the reaction product obtained in step (1) into a syringe with a needle diameter of 0.5 mm, fix it on a syringe pump, push the syringe, collect the injected liquid crystal elastomer fibers on a drum, and irradiate the liquid crystal elastomer fibers with ultraviolet light to further crosslink and solidify the liquid crystal elastomer fibers, so that the orientation of the liquid crystal unit is fixed. Since the diameter of the liquid crystal elastomer fibers is too small and the strength is low, they are easily damaged when removed from the drum, and it is difficult to bond them to the fiber membrane.
[0067] Embodiment 5:
[0068] (1) The liquid crystal unit RM257 was dissolved in THF to a final concentration of 0.2 g / mL, and 3,6-dioxa-1,8-octanedithiol and pentaerythritol tetrakis-3-mercaptopropionate were added in a molar ratio of 5:1, and the molar ratio of double bonds to thiol groups was 1.1:1. 1% by mass of benzil dimethyl ether and 0.4% by volume of di-n-propylamine catalyst were added and reacted at room temperature for 24 hours.
[0069] (2) Pour the reaction product obtained in step (1) into a syringe with a needle diameter of 1.1 mm, fix it on a syringe pump, push the syringe, and collect the injected liquid crystal elastomer fibers on a drum without ultraviolet irradiation.
[0070] (3) A polyurethane nanofiber membrane with a thickness of 0.5 mm was prepared by electrospinning, a liquid metal array was printed on its surface, and a layer of nanofiber membrane with a thickness of 0.1 mm was attached to protect the liquid metal; the liquid crystal elastomer fibers on the roller were collected and cut into fiber segments of the same length; and they were adhered to the fiber membrane at the position coated with the liquid metal array. Since the orientation of the liquid crystal unit was not fixed, after the voltage was applied to heat and deform, it could not return to its original shape when the voltage was disconnected and cooled, and could not be reversibly regulated. Figure 2 The stress-strain curve of liquid crystal elastomer fibers without further crosslinking.
[0071] Embodiment 6:
[0072] (1) The liquid crystal unit RM257 was dissolved in THF to a final concentration of 0.2 g / mL, and 3,6-dioxa-1,8-octanedithiol and pentaerythritol tetrakis-3-mercaptopropionate were added in a molar ratio of 5.5:1, and the molar ratio of double bonds to mercapto groups was 1.1:1. 1% of benzil dimethyl ether by mass and 0.4% of di-n-propylamine by volume were added as catalysts, and the reaction was carried out at room temperature for 24 hours.
[0073] (2) Pour the reaction product obtained in step (1) into a syringe with a needle diameter of 1.1 mm, fix it on a syringe pump, push the syringe, collect the injected liquid crystal elastomer fibers on a drum, and irradiate the liquid crystal elastomer fibers with ultraviolet light to further cross-link and solidify, thereby fixing the orientation of the liquid crystal unit.
[0074] (3) A first nanofiber membrane with a thickness of 0.2 mm is prepared by an electrospinning method (a polyurethane nanofiber membrane is selected in this embodiment), a liquid metal array is printed on its surface, and a second nanofiber membrane with a thickness of 0.1 mm is attached to protect the liquid metal; the liquid crystal elastomer fibers on the drum are collected and cut into fiber segments of the same length; the segments are adhered to the first nanofiber membrane at the position coated with the liquid metal array. Since the thickness of the first nanofiber membrane is too small and the strength is insufficient, wrinkles occur when voltage is applied to heat the liquid crystal elastomer, and the membrane shape cannot be maintained, resulting in an inability to obtain a deformable surface.
[0075] Embodiment 7:
[0076] (1) The liquid crystal unit RM257 was dissolved in THF to a final concentration of 0.2 g / mL, and 3,6-dioxa-1,8-octanedithiol and pentaerythritol tetrakis-3-mercaptopropionate were added in a molar ratio of 5:1, and the molar ratio of double bonds to thiol groups was 1.1:1. 1% by mass of benzil dimethyl ether and 0.4% by volume of di-n-propylamine catalyst were added and reacted at room temperature for 24 hours.
[0077] (2) Pour the reaction product obtained in step (1) into a syringe with a needle diameter of 1.1 mm, fix it on a syringe pump, push the syringe, collect the injected liquid crystal elastomer fibers on a drum, and irradiate the liquid crystal elastomer fibers with ultraviolet light to further cross-link and solidify, thereby fixing the orientation of the liquid crystal unit.
[0078] (3) Prepare a first nanofiber membrane with a thickness of 2 mm by electrospinning (a polyurethane nanofiber membrane is used in this embodiment), print a liquid metal array on its surface, and attach a second nanofiber membrane with a thickness of 0.1 mm to protect the liquid metal; collect the liquid crystal elastomer fibers on the drum, cut them into fiber segments of the same length; adhere them to the fiber membrane at the position coated with the liquid metal array. Since the first nanofiber membrane is too thick and too strong, it cannot deform along with the liquid crystal elastomer fibers when voltage is applied to heat the liquid crystal elastomer, and a deformable surface cannot be obtained.
[0079] Embodiment 8:
[0080] (1) The liquid crystal unit RM257 was dissolved in THF to a final concentration of 0.2 g / mL, and 3,6-dioxa-1,8-octanedithiol and pentaerythritol tetrakis-3-mercaptopropionate were added in a molar ratio of 5:1, and the molar ratio of double bonds to thiol groups was 1.1:1. 1% by mass of benzil dimethyl ether and 0.4% by volume of di-n-propylamine catalyst were added and reacted at room temperature for 24 hours.
[0081] (2) Pour the reaction product obtained in step (1) into a syringe with a needle diameter of 1.1 mm, fix it on a syringe pump, push the syringe, collect the injected liquid crystal elastomer fibers on a drum, and irradiate the liquid crystal elastomer fibers with ultraviolet light to further cross-link and solidify, thereby fixing the orientation of the liquid crystal unit.
[0082] (3) The first nanofiber membrane with a thickness of 0.5 mm is prepared by electrospinning (polyurethane nanofiber membrane is selected in this embodiment), and a liquid metal array is printed on its surface without a thin fiber membrane to protect the liquid metal; since the liquid metal is oxidized, it is easily damaged, resulting in circuit disconnection.
[0083] Embodiment 9:
[0084] (1) The liquid crystal unit RM257 was dissolved in THF to a final concentration of 0.2 g / mL, and 3,6-dioxa-1,8-octanedithiol and pentaerythritol tetrakis-3-mercaptopropionate were added in a molar ratio of 5:1, and the molar ratio of double bonds to thiol groups was 1.1:1. 1% by mass of benzil dimethyl ether and 0.4% by volume of di-n-propylamine catalyst were added and reacted at room temperature for 24 hours.
[0085] (2) Pour the reaction product obtained in step (1) into a syringe with a needle diameter of 1.1 mm, fix it on a syringe pump, push the syringe, collect the injected liquid crystal elastomer fibers on a drum, and irradiate the liquid crystal elastomer fibers with ultraviolet light to further cross-link and solidify, thereby fixing the orientation of the liquid crystal unit.
[0086] (3) A polyurethane nanofiber membrane with a thickness of 0.5 mm was prepared by electrospinning, a liquid metal array was printed on its surface, and a layer of fiber membrane with a thickness of 0.1 mm was attached to protect the liquid metal; the liquid crystal elastomer fibers on the drum were collected and cut into fiber segments of the same length; these segments were adhered to the fiber membrane at the position coated with the liquid metal array to obtain a voltage-controlled deformable surface. Figure 5 The height of the protrusions on the voltage-controlled deformable surface changes with time at a low voltage (1.1 V).
[0087] Embodiment 10:
[0088] Liquid crystal unit RM257 and graphene were dissolved in DMF to a final concentration of 0.2g / mL and 0.5mg / mL, respectively. 3,6-dioxa-1,8-octanedithiol and pentaerythritol tetra-3-mercaptopropionate were added in a molar ratio of 5:1, and the molar ratio of double bonds to thiol groups was 1.1:1. 1% mass fraction of benzil dimethyl ether and 0.4% volume fraction of di-n-propylamine catalyst were added and reacted at room temperature for 24 hours. The above reaction product was poured into a syringe and fixed on a syringe pump. The syringe was pushed and the injected liquid crystal elastomer fibers were collected on a drum. The liquid crystal elastomer fibers were further cross-linked and cured by ultraviolet light to obtain cured liquid crystal elastomer fibers with infrared light responsive properties; they were arrayed on a polyurethane nanofiber membrane with a thickness of 0.5mm to obtain a deformable surface regulated by infrared light.
[0089] It should be noted that in the above-mentioned embodiments of the present invention, other different schemes obtained by making specific selections within the scope of the steps, components, ratios and process parameters recorded in the present invention can all achieve the technical effects recorded in the present invention, so the present invention will no longer list them one by one.
[0090] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
[0091] The above embodiments are only used to illustrate the design ideas and features of the present invention, and their purpose is to enable those skilled in the art to understand the content of the present invention and implement it accordingly. The protection scope of the present invention is not limited to the above embodiments. Therefore, any equivalent changes or modifications made based on the principles and design ideas disclosed by the present invention are within the protection scope of the present invention.
Claims
1. A method for preparing a dynamically programmable surface, characterized in that: The method comprises the following steps: (1) adding 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene, 3,6-dioxa-1,8-octanedithiol, pentaerythritol tetrakis-3-mercaptopropionate and benzil dimethyl ether to an organic solvent, stirring evenly, adding di-n-propylamine, sealing, stirring at room temperature, and fully reacting to obtain a liquid crystal elastomer precursor solution; (2) Based on the liquid crystal elastomer precursor solution, the liquid crystal elastomer fibers are prepared by wet spinning technology, and the liquid crystal elastomer fibers are further cross-linked and cured by ultraviolet light; (3) Printing a liquid metal array on the surface of the first nanofiber membrane, and then attaching a second nanofiber membrane; collecting the liquid crystal elastomer fibers on the roller, and adhering them to the first nanofiber membrane at the position coated with the liquid metal array, thereby obtaining a voltage-controlled deformable surface.
2. The method for preparing a dynamically programmable surface according to claim 1, characterized in that: Also includes: 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene, 3,6-dioxa-1,8-octanedithiol, pentaerythritol tetrakis-3-mercaptopropionate, graphene and benzil dimethyl ether are added to an organic solvent, stirred evenly, and then di-n-propylamine is added, sealed, stirred at room temperature, and fully reacted; step (2) is repeated to obtain liquid crystal elastomer fibers with infrared light responsiveness; and the fibers are arrayed on a first nanofiber film to obtain a deformable surface regulated by infrared light.
3. The method for preparing a dynamically programmable surface according to claim 1, characterized in that: The step (1) is specifically: 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene is dissolved in an organic solvent to a final concentration of 0.2-0.25 g / mL, 3,6-dioxa-1,8-octanedithiol and pentaerythritol tetrakis-3-mercaptopropionate are added in a molar ratio of 4.5-5.5:1, and the molar ratio of double bonds to thiol groups is 1.1-1.15:1; benzil dimethyl ether is added to a mass fraction of 1%-2%, and a di-n-propylamine catalyst is added to a volume fraction of 0.3%-0.5%, and the reaction is carried out at room temperature for 24 hours.
4. The method for preparing a dynamically programmable surface according to claim 1, characterized in that: The step (2) is specifically: The reaction product in step (1) was poured into a syringe with a needle diameter of 0.9-1.1 mm, and the syringe was placed on a syringe pump, followed by extrusion at a pressure of 0.35 MPa and a speed of 1 mm / min, and collected on a roller with a rotation speed of 5 rpm, and further irradiated with ultraviolet light.
5. The method for preparing a dynamically programmable surface according to claim 1, characterized in that: The first nanofiber membrane and the second nanofiber membrane are both selected from the group consisting of a polyurethane nanofiber membrane, a polylactic acid nanofiber membrane and a polymethyl methacrylate nanofiber membrane.
6. The method for preparing a dynamically programmable surface according to claim 1, characterized in that: It also includes an ultraviolet curing device, which is a 365nm curing lamp to achieve the ultraviolet irradiation in step (2).
7. The method for preparing a dynamically programmable surface according to claim 1, characterized in that: The step (3) is specifically: A first nanofiber membrane with a thickness of 0.4-0.7 mm is prepared by electrospinning, a liquid metal array is printed on its surface, and a second fiber membrane with a thickness of 0.05-0.15 mm is attached to protect the liquid metal.
8. The method for preparing a dynamically programmable surface according to claim 1, characterized in that: The applied voltage of the voltage-regulated deformable surface is 0.5-1.1V.
9. The method for preparing a dynamically programmable surface according to claim 2, characterized in that: The final concentration of the graphene is 0.4-0.6 mg / mL; the wavelength of the infrared light is 0.76-5 um, and the intensity of the infrared light is 200 mW.
10. A dynamically programmable surface prepared according to the preparation method according to any one of claims 1 to 9, wherein the dynamically programmable surface comprises a voltage-controlled deformable surface and an infrared-controlled deformable surface.
Citation Information
Patent Citations
Preparation and application of force-induced conductive adhesive based on one-dimensional and two-dimensional materials
CN110527468A
Structural flexible electronic skin
CN110664512A
Bionic nano fiber material as well as preparation method thereof and application thereof
CN111793899A
Liquid metal-polymer composite soft actuator and preparation method thereof
CN113043288A
Liquid crystal elastomer material based on liquid metal nano-droplets
CN113698518A